EXAMINING THE RELATIONSHIP OF OLDER CARDIO-ONCOLOGY PATIENT FATIGUE SYMPTOM CLUSTERS AND CAREGIVER DEPRESSION. (11th November 2018) - Buck, H; Wang, H; Benitez, B; Fradley, M; Donovan, K; Reich, R
Abstract: Background: Co-occurring cancer and heart disease causes profound fatigue; a common, distressing symptom with implications for survival. Fatigue rarely occurs alone but rather in a cluster of symptoms. The impact on caregivers in this population is currently unknown. Objective: To examine the clustering of older adult patient fatigue-related symptoms and test a hypothesis of the impact of this cluster on caregivers. H: Patient fatigue-related symptom clusters (severity, distress) will be inversely associated with caregiver depression. Methods: Secondary analysis of a cardio-oncology sample from a multisite hospice study. Exploratory Factor Analysis was used to derive a fatigue-related symptom cluster from the Memorial Symptom Assessment Scale (severity, distress). Structural Equation Modeling was used to examine the relationship between the patient fatigue cluster and caregiver depression measured by the CES-D (10 items). Results: In a sample of 689 community-based patient/caregiver dyads (patient mean age 73, 56% male, 97% Caucasian; caregivers 66% spouses/partners, 19% adult children, 15% other). Patient fatigue clustered in a 3-factor solution (RMSEA = .04, RMR = .04, TLI = .86) with dry mouth, dyspnea, lack of appetite, drowsiness, dizziness, difficulty swallowing, cough. In unadjusted analyses, patient fatigue cluster severity was positively associated with caregiver depression (b = 0.12; RMSEA = 0.05, SRMR = 0.15, CFI = 0.92), but distress was not (p > .05). Conclusion: While individual patient symptoms have been examined in the cardio-oncology population, the impact of multiple symptoms on the informal caregiver has not been examined. This hypothesis testing study suggests that this impact is negative.